Rediscovering Europe in the Netherlands - Raad voor het Regeringsbeleid, Wetenschappelijke (WRR Rapporten, 2007)
The results of the 2005 referendum on the Constitutional Treaty for Europe exposed dramatically the rift between the political and public opinion regarding European policymaking. It also showed that politicians had failed to function as adequate links between "Europe" and the Dutch citizens. Against this background, the authors analyse the relative lack of legitimacy of the European Union in the Netherlands and advise on means of shoring up its image going beyond traditional institutional approaches. This title is available in the OAPEN Library - http://www.oapen.org.